PENGARUH LATIHAN LADDER DRILL TERHADAP KEMAMPUAN FOOTWORK PADA ATLET RENDY BADMINTON CLUB PEKANBARU - Widya Nesa Fathonah; Zainur Zainur; Ali Mandan (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract : The Problem in this study is that athletes often experience irregular patterns of paly when palying, so that Rendy Badminton Club Pekanbaru athletes finf it difficult to regulate the opponent’s defense and insert the shuttlecock into the opponent’s defense. The purpose of this study is to determine the effect of Ladder Drill on Footwork abilities in athletes at Rendy Badminton Club Pekanbaru. The population in this study were all athletes of Rendy Badminton Club Pekanbaru using a total sampling technique of 10 people. This Type of research uses a one group pree test post test design. From the result of this study, it can be conculed that the average result for Rendy Badminton Club Pekanbaruathletes is 29,91, based on the normal test, Lo maks Pree Test is 0,2483 < Ltabel 0,258, and Lo max Post Test is 0,2069 < Ltabel 0,258 which bet is normal distribution. Based on the statisticalanalysis of the t test, the different value is 1,55 and the tcount is 5,79 > ttabel 1.833. Means tcount > ttabel. It can be conculed that the Ladder Drill (X) exercie han an effect on Footwrok agility with Court Agiity Test (Y) on the athletes of Rendy Badminton Club Pekanbaru.Key Words: Ladder Drill practice,Court Agility Test, Badminton.